Percutaneous Spinal Interventions for Chronic Pain Management - McCormick, Robert; Shah, Sunali (Seminars in Neurology, 2023)
Chronic neck and back pain are two of the most common and disabling complaints seen in primary care and neurology practices. Most commonly these come in the form of cervical and lumbar radiculopathy, lumbar spinal stenosis, and cervical and lumbar facet arthropathy. Treatment options are widespread and include nonpharmacological, pharmacological, surgical, and interventional options. The focus of this review will be to discuss the most common interventional procedures performed for chronic cervical and lumbar back pain, common indications for performing these interventions, as well as associated benefits and risks. These interventions alone may not suffice to improve the quality of life in those suffering from chronic pain. However, an understanding of the interventional pain options available and the evidence behind performing these interventions can help providers incorporate these into a multimodal approach to provide effective pain management that may allow patients an improved quality of life.
Keywords: interventional pain; epidural; cervical; lumbar; radiculopathy